Optimizing Accounting and Tax Services with Business Plan Documents at Professional Start-up Tax Consultants - Ika Listiana Rahayu; Inanda Shinta Anugrahani (E-Jurnal Akuntansi, 2026)
This study analyzes the existing conditions of business processes at start-up accounting and tax consultants and develops a more structured and documented workflow. The analysis is based on a Research and Development (R&D) approach using the ADDIE model to develop a business plan document integrated with Standard Operating Procedures (SOPs). Business Process Management theory, internal control theory, and service quality management are used to interpret the relationship between process standardization, regulatory compliance, and the quality of operational governance implementation. The results of the study show that inadequate business processes tend to result in inconsistent work performance, weak control, and variations in service quality. The implementation of integrated SOPs can clarify workflows, division of responsibilities, and monitoring mechanisms, thereby improving governance quality, service reliability, and client trust.